TAHLIL KITAB MADRASI TA`ALIMI ALARABIAH BAINA YADAIK - Maimunah Dairani Lamri Banjar (UIN ANTASARI, 2019)
Abstract The schoolbook in general is important in the educational process and their own importance; given the role of the Arabic language in preserving the identity and culture of society, it is therefore necessary to pay attention to its design and preparation, so that it achieves the desired goals. It meets the standards and performance of the quality of the book and addresses the gap between the elements of the language and its skills. Teaching books include an important component in learning, therefore must meet the criteria of teaching books that are worth using in accordance with applicable provisions. And the teaching material in it is also good quality material. The purpose of this research is to find out the quality of the Arabic teaching book grade IV issued by the Ministry of Home Affairs in 2021. The methods used are library research and content analysis. Based on the results of the analysis can be known if there are still some errors in terms of content, presentation, language, and radiography. More research is needed on this book.Keywords: The School book _ standards _ goals _ skills. Teaching Book, Arabic